Circulating microRNAs May Serve as Biomarkers for Hypertensive Emergency End-Organ Injuries and Address Underlying Pathways in an Animal Model - Langlo, Knut Asbjørn Rise; Silva, Gustavo Jose Justo; Overrein, Tina Syvertsen; Adams, Volker; Wisløff, Ulrik; Dalen, Håvard; Rolim, Natale; Hallan, Stein Ivar (Frontiers in Cardiovascular Medicine, 2021)
There is an incomplete understanding of the underlying pathophysiology in hypertensive emergencies, where severely elevated blood pressure causes acute end-organ injuries, as opposed to the long-term manifestations of chronic hypertension. Furthermore, current biomarkers are unable to detect early end-organ injuries like hypertensive encephalopathy and renal thrombotic microangiopathy. We hypothesized that circulating microRNAs (c-miRs) could identify acute and chronic complications of severe hypertension, and that combinations of c-miRs could elucidate important pathways involved. We studied the diagnostic accuracy of 145 c-miRs in Dahl salt-sensitive rats fed either a low-salt (N=20: 0.3% NaCl) or a high-salt (N=60: 8% NaCl) diet. Subclinical hypertensive encephalopathy and thrombotic microangiopathy were diagnosed by histopathology. In addition, heart failure with preserved ejection fraction was evaluated with echocardiography and N-terminal pro-brain natriuretic peptide; and endothelial dysfunction was studied using acetylcholine-induced aorta ring relaxation. Systolic blood pressure increased severely in animals on a high-salt diet (high-salt 205±20 mm Hg vs. low-salt 152±18 mm Hg, p<0.001). Partial least squares discriminant analysis revealed 68 c-miRs discriminating between animals with and without hypertensive emergency complications. Twenty-nine c-miRs were strongly associated with hypertensive encephalopathy, 24 c-miRs with thrombotic microangiopathy, 30 c-miRs with heart failure with preserved ejection fraction, and 28 c-miRs with endothelial dysfunction. Hypertensive encephalopathy, thrombotic microangiopathy and heart failure with preserved ejection fraction were associated with deviations in many of the same c-miRs, whereas endothelial dysfunction was associated with a different set of c-miRs. Several of these c-miRs demonstrated fair to good diagnostic accuracy for a composite outcome of hypertensive encephalopathy, thrombotic microangiopathy and heart failure with preserved ejection fraction in receiver-operating-curve analyses (area-under-curve 0.75-0.88). Target prediction revealed an enrichment of genes related to several pathways relevant for cardiovascular disease (e.g. mucin type O-glycan biosynthesis, MAPK, Wnt, Hippo, and TGF-beta signaling). C-miRs could potentially serve as biomarkers of severe hypertensive end-organ injuries and elucidate important pathways involved.